2021
DOI: 10.3390/pr9050890
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Irradiation Drying Impact on Bee Pollen: Case Study on the Phenolic Composition of Eucalyptus globulus Labill and Salix atrocinerea Brot. Pollens

Abstract: Bee pollen is commonly reputed as a rich source of nutrients, both for bees and humans. Its composition is well balanced and can be taken as a stand-alone food or as supplement, including for the elderly owing its low caloric value. However, storage conditions frequently lead to product degradation, namely due to the high moisture content that enable the proliferation of molds and bacteria. Herein, an infrared (IR)-based technology is proposed as a mean to determine moisture content, setting also a new scalabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…BP’s richness in nutrients, such as proteins, vitamins, minerals, oligo-elements, and unsaturated fatty acids, is certain, along with the fact that it provides a moderate calorie intake as well as a good level of tolerance and safety, except for in the case of allergic reactions or external pollution, which remain manageable and predictable. BP hazards can arise mainly from external contamination factors, as pollen is very sensitive to these factors [ 2 ], or from inconvenient storage and processing conditions [ 1 ]. Special requirements are being established in the ISO-TC34-SC19-WG3 norm to avoid such tampering in the quality assurance and control of the crude material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BP’s richness in nutrients, such as proteins, vitamins, minerals, oligo-elements, and unsaturated fatty acids, is certain, along with the fact that it provides a moderate calorie intake as well as a good level of tolerance and safety, except for in the case of allergic reactions or external pollution, which remain manageable and predictable. BP hazards can arise mainly from external contamination factors, as pollen is very sensitive to these factors [ 2 ], or from inconvenient storage and processing conditions [ 1 ]. Special requirements are being established in the ISO-TC34-SC19-WG3 norm to avoid such tampering in the quality assurance and control of the crude material.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial research has been conducted on the composition and pharmacological bioactivities of bee pollen (BP), indicating both its usefulness and safety. Numerous studies have shown that BP has a rich and well-balanced composition to serve as a human food and supplement, while its richness of bioactive compounds, especially polyphenols, confers to it a large array of biological and pharmacological activities [ 1 ]. BP-related risks may mainly emanate from external factors [ 2 ], or from improper storage and processing conditions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen can be supplemented in a healthy diet, offering a significant daily intake of nutrients because of its superior nutrient profile. Even elderly persons can consume it as a stand-alone diet or supplement, because of its nutritionally balanced composition and low-calorie count (Campos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Campos et al, [1] discuss the drying impact on the phenolic composition of pollens of Eucalyptus globulus and Salix atrocinerea plant models by using infrared irradiation technology. This technique is used to determine the moisture content in pollens.…”
mentioning
confidence: 99%